Effects of fly ash and slag content on the solidification of river-dredged sludge. Issue 1 (2nd January 2021) - Liu, Feiyu; Zhu, Chengan; Yang, Kejun; Ni, Junfeng; Hai, Jun; Gao, Shihu
Abstract: River-dredged sludge has a high water content and minimal bearing capacity and strength. Adding cement, fly ash, and slag to dredged sludge as a combined curing agent can quickly reduce its water content and improve its strength. This study experimentally investigates the solidification effectiveness of different proportions of curing agents using methods including electron microscopy, particle size analysis, water ratio limit, and water content and direct shear tests. The water content and shear strength of different combined curing agents are obtained at different ages. We find that an optimum curing agent combination exists. With increases in fly ash and slag content, test results indicate that the water content of solidified sludge first decreases and then increases, whereas the shear strength first increases and then decreases, allowing an optimal combination curing agent to be obtained. When using industrial waste residue as curing agent, it is necessary to consider the negative effects of the curing agent to better control the dosage so as to achieve better curing effect.